2013
DOI: 10.2337/db12-1762
|View full text |Cite
|
Sign up to set email alerts
|

Very Low–Calorie Diet Mimics the Early Beneficial Effect of Roux-en-Y Gastric Bypass on Insulin Sensitivity and β-Cell Function in Type 2 Diabetic Patients

Abstract: Marked improvement in glycemic control occurs in patients with type 2 diabetes mellitus shortly after Roux-en-Y gastric bypass surgery (RYGB) and before there is major weight loss. The objective of this study was to determine whether the magnitude of this change is primarily due to caloric restriction or is unique to the surgical procedure. We studied eleven subjects who underwent RYGB and fourteen subjects mean-matched for BMI, HbA1c, and diabetes duration who were admitted to our inpatient research unit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
197
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(223 citation statements)
references
References 41 publications
23
197
0
3
Order By: Relevance
“…After RYGB, a 2.6-fold increase of insulin secretion assessed by the intravenous glucose tolerance test disposition index has been reported (34). A very lowcalorie diet or RYGB results in similarly increased insulin secretion in both groups despite a marked increase in GLP-1 after RYGB only (35). A specific GLP-1 receptor antagonist does not affect insulin secretion after RYGB (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…After RYGB, a 2.6-fold increase of insulin secretion assessed by the intravenous glucose tolerance test disposition index has been reported (34). A very lowcalorie diet or RYGB results in similarly increased insulin secretion in both groups despite a marked increase in GLP-1 after RYGB only (35). A specific GLP-1 receptor antagonist does not affect insulin secretion after RYGB (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…4 Obese patients with T2D who underwent RYGB or 500 kcal/day diet lost equivalent weight over three weeks and showed similar improvements in acute insulin secretion and beta-cell function in an IV GTT. 65 Postprandial GLP-1 secretion is substantially and durably increased early after RYGB, before significant weight loss has occurred, due to increased delivery of nutrients to the distal small intestine. 127 The importance of the incretin effect is unclear, with some studies showing that GLP-1 receptor blockade abolishes the RYGB-related improvement in beta-cell glucose sensitivity and insulin secretion 127 while another study found only minimal impairment in glucose tolerance following GLP-1 blockade after RYGB.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…4,64 VLCD leads to a reduction in fasting plasma glucose within the first days -when weight loss is minimal -largely attributable to reduced hepatic glucose output. 4,65 This is associated with reduced basal insulin secretion, suggesting improved hepatic insulin sensitivity. 4,65 It would be predicted that reduction in FPG would improve beta-cell function by amelioration of glucotoxicity and, in overweight patients with T2D, eight weeks of VLCD can lead to a gradual restoration of first-phase insulin response.…”
Section: Very Low Calorie Diet (Vlcd)mentioning
confidence: 99%
See 1 more Smart Citation
“…In studies with bariatric surgery patients, it is standard procedure to provide a very low calorie diet for a week or two after gastric bypass surgery [19][20][21] and caloric intake is often also restricted before surgery. In addition, patients typically receive heavy dietary counseling before and after surgery, making it difficult to analyze quantity and pattern of voluntarily ingested food, particularly during the early post-surgical period.…”
Section: Behavioral Evidence For Rygb-induced Change In Defended Bodymentioning
confidence: 99%